2004
DOI: 10.1002/ppul.20018
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences among children 2–13 years of age presenting at the emergency department with acute asthma

Abstract: Hospitalization rates for asthma have been reported to be higher in males than females in children under age 15, but it is not clear whether this disparity reflects gender differences in prevalence, severity, or treatment. We performed a prospective cohort study as part of the Emergency Medicine Network. Patients aged 2-13 years who presented to the emergency department (ED) with acute asthma underwent a structured interview in the ED and another by telephone 2 weeks later. Of 1,602 patients, 61% (95% CI, 59-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…The prevalence of the use of asthma medication and of symptoms common in asthma, including attacks of shortness of breath, recurrent wheeze and long-standing cough, was higher in women than in men. This is in agreement with the well-known shift after puberty, when asthma becomes more prevalent in women than in men (2,25).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of the use of asthma medication and of symptoms common in asthma, including attacks of shortness of breath, recurrent wheeze and long-standing cough, was higher in women than in men. This is in agreement with the well-known shift after puberty, when asthma becomes more prevalent in women than in men (2,25).…”
Section: Discussionsupporting
confidence: 91%
“…Although in the current study eosinophil counts were not assessed as a risk factor, it was demonstrated that the proportion of patients experiencing ≥1 exacerbations during the follow-up period was higher in patients who had severe uncontrolled asthma (GINA Step 4/5 plus ≥2 exacerbations in the previous year) with eosinophil counts (≥300 cells/μl) than in patients who did not. The current study also demonstrated that females had a higher exacerbation risk than males, a result demonstrated in a previous study, [20] although not all studies are in agreement [21]. …”
Section: Discussionsupporting
confidence: 83%
“…Concurrently, among children presenting to an Emergency Department (ED), there does not seem to be any difference in admission rates for boys or girls, and no sex differences for relapse or ongoing exacerbation (40). This suggests that asthma is not inherently more severe in boys with asthma compared to girls, and that the increased rate of hospitalizations in young boys is due to differences in prevalence, not severity.…”
Section: Resultsmentioning
confidence: 96%